Structure investigation of the recovered zinc sulfide from fulfilled electron-excited phosphorus - Завгородня, Наталія Ігорівна (Technology audit and production reserves, 2014)
Some investigation results of recovered zinc sulfide from electron-excited phosphorus of fulfilled television picture tubes and computer monitors is shown in the article. The purpose of investigation is determination of modification type of crystal structure, investigation of some its characteristics and behavior of recovered zinc sulfide. For this purpose the crystalline precipitate of recovered zinc sulfide obtained from electron-excited phosphorus solutions in an aqueous solution of hydrochloric acid by deposition method. The processes of dehydration and crystallization are investigated by thermographic, differential - thermal, chemical and X-ray diffraction analysis methods. It is possible to determine the type of structural modifications of recovered zinc sulfide and also explore the behavior of recovered substances in aqueous solutions. Complex of physical and chemical properties of recovered zinc sulfide can be used as semiconducting compound. Zinc sulfide recovery from electron-excited phosphorus of fulfilled television picture tubes and computer monitors from aqueous solutions by precipitation allow to establish basic patterns of behavior in these solutions, to identify the sphalerite modification of zinc sulfide.